Efeitos do Exercício Físico Aquático em Idosos da comunidade nos Fatores Motores de Risco de Quedas: Um Ensaio Clínico Randomizado - Daniela Lemes Ferreira (2021)
Introduction: Population aging is a worldwide phenomenon and it is associated with physiological changes, which can lead to increased disability, frailty and increased risk of falls. Reductions of muscle strength, flexibility and stability are potentially modifiable motor risk factors for falls, providing a logic to create interventions aimed to improve these performances. In this sense, aquatic physical exercise provides challenging situations that favor training of mobility, muscle strength and postural stability in a safe way and it can be a great resource for preventing falls. Objectives: To verify the effects of an aquatic physical exercise protocol on potentially modifiable motor risk factors for falls in community-dwelling older people. Method: A randomized, single-center, controlled clinical trial was carried out with 49 non-active older people aged 65 and over years old, without cognitive impairment. They were divided into two groups (Aquatic Training Group ATG and Control Group CG) and there were two evaluation moments (m1 = initial, m2 = after 16 weeks of training). Muscle strength was assessed by the 5 times sit to stand test; mobility by the simple and double-task Timed and Go (TUG) test; and postural stability through the stabilometric data obtained by the force platform. The CG received monthly calls to monitor general health. The ATG carried out a training lasting16 weeks, with two 1-hour sessions per week, on non-consecutive days. The intensity was gradually progressed according to the Modified Borg Effort Perception Scale (BORG-CR10) (0 to 10 points). Data were analyzed using the Chi-square test, independent t test and two-way ANOVA test, using a significance level of α = 0.05 and the SPSS software (20.0). Results: At baseline, 52 older people were evaluated and, after 16 weeks, 49 participants were reassessed (ATG:n=24; CG: n=25). In the total sample, both groups improved performance of muscular strength and cognitive-motor task and they performed the dual task with less error in the secondary task. There was a significant decrease after 16 weeks of the center of pressure area in the upright posture, with closed eyes and feet in tandem position in the CG. The CG presented higher mean velocity of lateral displacement of the center of pressure in the upright posture, with open eyes and feet in tandem position in both assessments. Conclusion: Aquatic physical exercise is a great resource for improving motor risk factors for falls, especially muscle strength and mobility, but further research with greater adherence are suggested. Keywords: aged, physical exercise, falls, hydrotherapy